2013
DOI: 10.1007/s00776-013-0432-z
|View full text |Cite
|
Sign up to set email alerts
|

The Pavlik harness in the treatment of developmentally dislocated hips: results of Japanese multicenter studies in 1994 and 2008

Abstract: BackgroundIt has already been more than 50 years since the Pavlik harness was introduced in Japan, and today the Pavlik harness is widely recognized as the standard initial treatment modality for developmental dysplasia of the hip. We performed a multicenter nationwide questionnaire study concerning the results of Pavlik harness treatment twice in 1994 and 2008.MethodsIn 1994 and in 2008, we sent questionnaires to 12 institutes in Japan specializing mainly in pediatric orthopedics. We compare the results of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 21 publications
1
9
0
1
Order By: Relevance
“…Infants between three and six months of age and CSHD grade IV hips had higher rates of failure and ON. 20 In a multicentre study from Japan 22 including nearly 4000 hips with complete dislocations (mean treatment initiation ages range from 3.5 to 4.8 months) that were followed until skeletal maturity, the rate of hip relocation by Pavlik’s method was around 80%, the rate of ON was about 11% and a satisfactory radiographic outcome without any additional osteotomies in the long-term follow-up was obtained in about 75% of the hips. The overall success rates in other studies ranged from 45% to 100% and in about two-thirds of these studies it was more than 75%.…”
Section: Results Of Treatmentmentioning
confidence: 99%
“…Infants between three and six months of age and CSHD grade IV hips had higher rates of failure and ON. 20 In a multicentre study from Japan 22 including nearly 4000 hips with complete dislocations (mean treatment initiation ages range from 3.5 to 4.8 months) that were followed until skeletal maturity, the rate of hip relocation by Pavlik’s method was around 80%, the rate of ON was about 11% and a satisfactory radiographic outcome without any additional osteotomies in the long-term follow-up was obtained in about 75% of the hips. The overall success rates in other studies ranged from 45% to 100% and in about two-thirds of these studies it was more than 75%.…”
Section: Results Of Treatmentmentioning
confidence: 99%
“…1,2 Early detection and treatment of dislocation related to DDH (DDH-dislocation) are highly effective, with >80% success rates. [3][4][5][6] However, treatment outcomes in patients diagnosed with DDH-dislocation at the age of ≥1 year vary, 7,8 suggesting that early detection and treatment are essential for good outcomes in patients with DDH-dislocation. In the 1960s and 1970s, the incidence of DDH-dislocation in Japan was estimated at 1−3%.…”
Section: A C C E P T E D V E R S I O Nmentioning
confidence: 99%
“…The overall rate of ON in the entire study population, however, was less than 1%, leading to widespread adoption of this new "functional method" of treatment [18]. We found 16 studies to be included in this review [8][9][10][19][20][21][22][23][24][25][26][27][28][29][30][31]. Two large, multi-center studies have reported outcomes following Pavlik Harness treatment.…”
Section: Complications Following Pavlik Harness Treatmentmentioning
confidence: 99%
“…The overall rate of ON in the entire study population, however, was less than 1%, leading to widespread adoption of this new “functional method” of treatment [ 18 ]. We found 16 studies to be included in this review [ 8 10 , 19 31 ].…”
Section: Complications Following Pavlik Harness Treatmentmentioning
confidence: 99%